Microwave-etched V2C MXene-activated carbon hybrid as a high-performance anode material for lithium-ion batteries - Fathihah Nabila, Mohammad Azlan *; Muhammad Amirul, Aizat Mohd Abdah *; Tan, Yee Seng *; Muhammad Norhaffis, Mustafa *; Rashmi, Walvekar; Mohammad, Khalid * (Elsevier, 2023)
Activated carbon (AC) has been widely utilized as an active material in lithium-ion batteries (LIB) due to its stability and abundance. Nevertheless, the performance of AC anode materials alone falls short of competing with hybrid anode materials, which can attain maximum discharge capacity. Recently, a new two-dimensional (2D) transition metal carbide, MXene, has shown promising performance as an anode in LIB applications. The combination between AC and MXene has proved to improve battery performance previously. Thus, in this study, the electrode was prepared using a hybrid of activated carbon with vanadium carbide MXene (V2C), which was synthesized by etching V2AlC with in situ of hydrochloric acid (HCl) and lithium fluoride (LiF) at 90 °C for 30 min via microwave-assisted hydrothermal technique. The characterization by XRD pattern shows the appearance of V2C MXene peak at 7.23°, indicating the successful etching from V2AlC MAX. The as-prepared AC/V2C_D at ratio 9:1 revealed excellent electrochemical properties as anode LIB, owned capacity up to 562 mAh g−1 (at 50 mA g−1) with cycling stability and columbic efficiency of 95.87 % and 98.2 %, respectively after 50 cycles. Moreover, AC/V2C_D exhibited the smallest Rct (18.50 Ω), and the discharge capacity of 370.25 mAh g−1 was restored after 60 cycles when the current density returned to 50 mAg−1, implying a good reversibility performance and high endurance for LIB. Furthermore, the fabricated full cell of AC/V2C_D//LiFePO4 exhibits initial discharge and charge capacity at 159.6 and 199.8 mAh g−1, respectively, with 79.9 % of CE and delivers a stable cycling performance with reversible discharge specific capacity of 82.72 mAh g−1 after 100 cycles. These promising results prove that the hybrid of AC/V2C_D MXene can be good potential as an anode material in future LIBs applications.